(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Natural fragrances are perfumes created from environment friendly, natural, and organicmaterials. The aromatic compounds included in these natural fragrances are used by the human bodyeither via the skin or through the sense of smell. Due to the low toxicity of these chemicals and the risingconsumer knowledge of the usage of natural and synthetic perfumes, these fragrances are in highdemand. Due to growing health awareness, fragrance consumers are choosing natural goods toguarantee better lives. The majority of consumers seeking natural fragrances are adults and seniors. Theworldwide market for natural fragrances is being driven by changing consumer behaviour, expandingactivities for sourcing ingredients, and certification. Natural sources continue to provide flavour andfragrance elements that are distinctive and efficient, despite the widespread usage of flavour and scentfrom artificial sources. Traditional harvesting of wild crops and fermentation of natural substratesutilizing cutting-edge biotechnological processes are two different production methodologies. Researchinto the chemistry of natural product analysis advances our knowledge and enjoyment of the substancesin the fragrance industry.